2016
DOI: 10.1177/1077801216675742
|View full text |Cite
|
Sign up to set email alerts
|

When Wife-Beating Is Not Necessarily Abuse: A Feminist and Cross-Cultural Analysis of the Concept of Abuse as Expressed by Tibetan Survivors of Domestic Violence

Abstract: This article describes the views of Tibetan women who have experienced physical violence from male intimate partners. How they conceptualise abuse, their views on acceptable versus unacceptable hitting, and the acts besides hitting which they felt to be unacceptable or abusive, are explored. Views of survivors' relatives/friends and men who have hit their wives are also included. Western-based domestic violence theory is shown to be incommensurate with abuse in particular socio-cultural settings. As feminist s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
21
0
1

Year Published

2019
2019
2021
2021

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 21 publications
(25 citation statements)
references
References 43 publications
3
21
0
1
Order By: Relevance
“…Violence in itself was considered a relatively acceptable matter. 91 Furthermore, it has been shown that women who have experienced violence in the household usually choose not to disclose it to or seek help from others. The National Family Health Survey in India (2014/2015) showed that only 14% of women who had ever experienced violence had sought help; among whom only 1% sought help from doctor or medical personnel.…”
Section: Discussionmentioning
confidence: 99%
“…Violence in itself was considered a relatively acceptable matter. 91 Furthermore, it has been shown that women who have experienced violence in the household usually choose not to disclose it to or seek help from others. The National Family Health Survey in India (2014/2015) showed that only 14% of women who had ever experienced violence had sought help; among whom only 1% sought help from doctor or medical personnel.…”
Section: Discussionmentioning
confidence: 99%
“…Research is needed to identify cross-cultural distinctions in the consequences of forgiveness (and unforgiveness), given that conceptualisations and tolerance of IPV differ across societies, cultures and ethnic groups. For example, Rajan's 45 qualitative study involving a Tibetan group of victims, friends/relatives of victims, and perpetrators of physical partner abuse identified conditions in which abuse was perceived to be acceptable, or even justified. Along similar lines, based on evidence highlighting the role of third parties in the forgiveness process 46 , it would be prudent to explore the relevance and impact of broader social influences (i.e.…”
Section: Limitations and Future Research Directionsmentioning
confidence: 99%
“…However, interpretations of acceptance of domestic violence might be associated with women’s agency and capacity to leave an abusive relationship. Rajan (2018) found that women did not really accept being hit or beaten, but they labeled violence as acceptable only because they did not believe leaving their abusive relationships was a possibility.…”
Section: Perception Acceptance and Justification Of Domestic Violencementioning
confidence: 99%
“…Muslim women, including Afghan women, are creating their interpretations in complex discourses to identify abusive actions (Mahmood, 2011; Rajan, 2018). However, interpretations of acceptance of domestic violence might be associated with women’s agency and capacity to leave an abusive relationship.…”
Section: Perception Acceptance and Justification Of Domestic Violencementioning
confidence: 99%